NIGERIAN NEWSPAPERS’ COVERAGE OF CLIMATE CHANGE ISSUES - Nwabueze, Chinenye; Nnaemeka, Frank; Umeora, Dubem (European Scientific Journal, ESJ, 2015)
This study is a content analysis of three national Dailies (Vanguard, Guardian and Daily Sun Newspapers) to determine the coverage of climate change issues for a period of four months. The objectives of this study are to determine the volume of coverage of climate change issues, to find out the forms in which climate change issues were presented in the media and to determine the event/fora that drives the coverage of climate change issues by the Nigerian newspapers. The units of analysis of the study are volume of coverage, story type/forms of presentation, and fora/forum forms that brought about the media coverage of climate charge issue, while the content categories are straight news reports, feature stories, cartoons, advertorials, editorials and letters to the editor. Sample size for the study was 190. It was found that the volume of coverage of the issue is poor and that the dominant form of presentationwas feature stories. It was also found that most of the stories on climate change reported in the Nigerian media were based on specific events on climate change. It was recommended among others that Nigerian press should give priority attention to the coverage of climate change issues as regular communication about it is the first step towards developing coping mechanisms in Nigeria.